Isolated Fallopian Tube Torsion in Adolescents. (22nd October 2013) - Rajaram, S.; Bhaskaran, S.; Mehta, S.
Abstract : Background . Fallopian tube torsion is a rare cause of acute abdomen, occurring commonly in females of reproductive age. It lacks pathognomonic symptoms, signs, or imaging features, thus causing delay in surgical intervention. Case . We report two cases of isolated fallopian tube torsion in adolescent girls. In the first case a 19-year-old patient presented with acute pain in the left iliac region associated with episodes of vomiting for one day and mild tenderness on examination. Laparoscopy revealed left sided twisted fallopian tube associated with hemorrhagic cyst of ovary. The tube was untwisted and salvaged. In another case an 18-year-old virgin girl presented with similar complaints since one week, associated with mild tenderness in the lower abdomen and tender cystic mass on per rectal examination. On laparoscopy right twisted fallopian tube associated with a paratubal cyst was found. Salpingectomy was done as the tube was gangrenous. Conclusion . Fallopian tube torsion, though rare, should be considered in women of reproductive age with unilateral pelvic pain. Early diagnostic laparoscopy is important for an accurate diagnosis and could salvage the tube.